Pressure-induced commensurate stacking of graphene on boron nitride - Yankowitz, Matthew; Watanabe, K.; Taniguchi, T.; San-Jose, Pablo; LeRoy, Brian J. (Nature communications, 2016)
Combining atomically-thin van der Waals materials into heterostructures provides a powerful path towards the creation of designer electronic devices. The interaction strength between neighbouring layers, most easily controlled through their interlayer separation, can have significant influence on the electronic properties of these composite materials. Here, we demonstrate unprecedented control over interlayer interactions by locally modifying the interlayer separation between graphene and boron nitride, which we achieve by applying pressure with a scanning tunnelling microscopy tip. For the special case of aligned or nearly-aligned graphene on boron nitride, the graphene lattice can stretch and compress locally to compensate for the slight lattice mismatch between the two materials. We find that modifying the interlayer separation directly tunes the lattice strain and induces commensurate stacking underneath the tip. Our results motivate future studies tailoring the electronic properties of van der Waals heterostructures by controlling the interlayer separation of the entire device using hydrostatic pressure. Van der Waals heterostructures enable fabrication of materials with engineered functionalities. Here, the authors demonstrate precise control over the interaction between layers by application of pressure with a scanning tunnelling microscopy tip.